2016
DOI: 10.1136/esmoopen-2016-000038
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio (NLR) for prediction of distant metastasis-free survival (DMFS) in early breast cancer: a propensity score-matched analysis

Abstract: ObjectiveTo assess the correlation between presurgery neutrophil to lymphocyte ratio (NLR) and distant metastasis-free survival (DMFS) in patients with early breast cancer.DesignRetrospective analysis.Participants300 Caucasian patients with early (T1–2, N0–1, non-metastatic) breast cancer who were followed from July 1999 to June 2015 at our Institution.Main outcome measuresDistant metastasis-free survival (DMFS).ResultsOf whole populations (300 patients), 134 and 166 patients were grouped as low and high NLR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 43 publications
7
58
0
2
Order By: Relevance
“…Similar to elevated platelet count, high PLR has been found to be associated with worse survival in a variety of solid (hepatocellular, ovarian, cervix, colorectal, bile duct, breast, lung, renal cell, gastric, prostate, and oesophageal) tumours [30][31][32][33][34][35][36][37][38][39][40]. Moreover, several studies confirmed the relationship between elevated NLR and a worse prognosis in patients with malignant oesophageal [41], colorectal [42,43], pancreas [44,45], prostate [46,47], hepatic [48,49], bile duct [50], breast [51], gastric [52,53], cutaneous melanocytic [54], thyroid medullary [55], and lung [56] tumours. It is important to note, however, that NLR may be elevated also in many benign disorders [57,58].…”
Section: Discussionmentioning
confidence: 93%
“…Similar to elevated platelet count, high PLR has been found to be associated with worse survival in a variety of solid (hepatocellular, ovarian, cervix, colorectal, bile duct, breast, lung, renal cell, gastric, prostate, and oesophageal) tumours [30][31][32][33][34][35][36][37][38][39][40]. Moreover, several studies confirmed the relationship between elevated NLR and a worse prognosis in patients with malignant oesophageal [41], colorectal [42,43], pancreas [44,45], prostate [46,47], hepatic [48,49], bile duct [50], breast [51], gastric [52,53], cutaneous melanocytic [54], thyroid medullary [55], and lung [56] tumours. It is important to note, however, that NLR may be elevated also in many benign disorders [57,58].…”
Section: Discussionmentioning
confidence: 93%
“…(2) Patients Receiving Adjuvant Treatment Twenty-three studies reported data on NLR as a prognostic factor in patients with localized BC receiving adjuvant treatment . Most studies (n = 18; 78%) included patients with all BC molecular subtypes [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. four included only patients withTNBC [49][50][51][52], and one work included patients with onlyhormone receptor-negative BC (independently of the HER2 status) [53].…”
Section: Results On Other Inflammatory Blood Markersmentioning
confidence: 99%
“…Studies including All BC Molecular Subtypes: seventeen studies analyzed the correlation between NLR and DFS after adjuvant chemotherapy [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In the univariate analysis, NLR was correlated with DFS in 14/17 articles (82%) [34,35,[37][38][39][40][41][42][44][45][46]46,47].…”
Section: Results On Nlr and Dfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a low NLR predicted for better OS and DFS (HR was 1.6 and 1.5, respectively) (Jia et al, 2015). Other studies also demonstrated a NLR/DFS association (Orditura et al, 2016).…”
Section: Characteristicsmentioning
confidence: 94%